The Relationship between the Lee Score and Postoperative Mortality in Patients with Proximal Femur Fractures - Guerra, Marcelo Teodoro Ezequiel; Giglio, Luiz; Morais, João Mauro Mendina; Labatut, Giovanna; Feijó, Monica Cavanus; Kayser, Carlos Eduardo Peixoto (Revista Brasileira de Ortopedia, 2019)
Objective To verify the predictive value of the Lee score for mortality in a one-year period after proximal femur fracture surgery. The present study also evaluated the isolated predictive capacity of other variables.Methods A sample of 422 patients with surgically-treated proximal femur fractures was evaluated. Data was collected through a review of medical records, appointments, and contact by telephone.Results The Lee score was applied to 99.3% of the patients with proximal femur fractures submitted to surgical treatment. The mortality rate was of 22% of the sample, and the majority were classified as class I risk. The Lee score had no significant association with mortality (p = 0.515). High levels of serum creatinine (p = 0.001) and age (p = 0.000) were directly associated with death.Conclusion The Lee score was not predictive of mortality in a one-year period after proximal femur fracture surgery; however, a statistical significance was observed between age and serum creatinine levels, considered separately, and death.
Keywords: femoral fractures/etiology; femoral fractures/surgery; femoral fractures/mortality; postoperative complications